Urgensi Perpustakaan IAIN Pare - Pare Dalam Meningkatkan Literasi Mahasiswa Fakultas Tarbiyah IAIN Pare-Pare - Ahdar; Usman; Sukma (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
The urgency of the IAIN Parepare library for tarbiyah faculty students is one of the places to study and add insight. With the existence of a library, students can use the container to be used as a recreation area and look for reading references to support their literacy. This research is a type of qualitative research. The targets in this study were tarbiyah faculty students and library managers at IAIN Parepare. Data collection techniques were carried out through observation and interviews, equipped with data analysis techniques using data reduction and data presentation. The results of this study indicate that: 1) The use of libraries to improve student literacy at the Tarbiyah Faculty of IAIN Parepare, namely library development is a student need. 2) Increasing the literacy of Tarbiyah students of IAIN Parepare through the use of libraries, namely literacy as a supplement to improve students' mindsets and reasoning